2016
DOI: 10.1016/j.jacc.2016.03.133
|View full text |Cite
|
Sign up to set email alerts
|

TCTAP A-105 Coronary Slow Flow Phenomenon (CSFP) – Assessment of the Role of Endothelial Dysfunction

Abstract: RESULTS A total of 168 patients were studied. 70 patients were excluded due to various causes such as smoking, diabetes etc. The remaining 98 patients underwent final assessment. A majority of these patients, that is, 57 patients showed impaired vasodilation. This is a strong and indirect evidence for endothelial dysfunction.CONCLUSION Majority of the patients diagnosed as cardiac syndrome X, had impaired flow mediated dilation of the artery. This is a strong and indirect evidence for endothelial dysfunction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ramakrishnan et al (10) reported that dyslipidemia, smoking, and hypertension were significantly associated with SCF and recommended endothelial dysfunction as a significant contributor in SCF phenomenon. Similarly, in a study by Sanati et al (11) , it was concluded that low level of high hyperalphalipoproteinemia (HDL-c) and hypertension were independent predictors of SCF phenomenon.…”
Section: Figure (2): Roc Curve For Suggested Slow Flow Cutoff Regard ...mentioning
confidence: 99%
“…Ramakrishnan et al (10) reported that dyslipidemia, smoking, and hypertension were significantly associated with SCF and recommended endothelial dysfunction as a significant contributor in SCF phenomenon. Similarly, in a study by Sanati et al (11) , it was concluded that low level of high hyperalphalipoproteinemia (HDL-c) and hypertension were independent predictors of SCF phenomenon.…”
Section: Figure (2): Roc Curve For Suggested Slow Flow Cutoff Regard ...mentioning
confidence: 99%